Approaches to starting and growing ERAS at a Children's Hospital - Kyle O. Rove; Megan A. Brockel (Elsevier, 2024)
Enhanced Recovery After Surgery is a multi-disciplinary, multi-modal, evidence-based approach to perioperative care that is known to improve outcomes for adult patients and has more recently been shown to lead to similar improvements for children. Its success in adult patients has led to growing interest in the adoption of ERAS in the pediatric population. Successful ERAS implementation hinges on strong leadership, provider and patient education and engagement, and continuous audit with the use of quality improvement methodology. The electronic health record is an invaluable tool that can be leveraged to not only aid in delivering standardized care through order sets for medications, fluids, and daily cares, but also to document and audit process measures and outcomes. In this paper, the authors describe our 10-year journey at a free-standing children's hospital from initial "baby steps" implementing individual elements for a single surgery to 11 active, comprehensive protocols spanning eight specialties and growing.